Manajemen Pembelajaran Multikultural Untuk Menumbuhkan Nilai-Nilai Karakter Anak Melalui Konsep Tri N (Niteni, Nirokke, Nambahi) Di Kelompok Bermain Vanda Perta Rini Kalasan Sleman - Sri Lestari; Sunarto Sunarto (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to identify and analyze multicultural-based learning management to foster children's character values ​​through the concepts of niteni, nirokke, nambahi at KB Vanda Perta Rini Kalasan Sleman. The research method used is qualitative with data collection techniques using interviews, observation and documentation. Processing and analysis of data using data reduction, data presentation and drawing conclusions. Information was obtained from respondents, namely school principals, vice curricula, and class teachers. The data validation technique uses data triangulation techniques. The results of the study can be concluded in several ways, namely (1) Multicultural-based learning management at KB Vanda Perta Rini begins with planning a work program that is arranged in a work meeting in the form of a work plan. The organization at the Vanda Perta Rini KB is carried out in a kinship system with a system that refers to the applicable SOPs. The implementation of the work program is carried out by referring to the previously planned work program. Supervision is carried out centrally by the school principal and is recorded and reported in July or at the start of the new school year to the foundation. It is known that the results of the program evaluation show that 70-100% are fulfilled or the results are developing according to expectations for the category of evaluation of learning related to child development. (2) The learning process with the Tri N concept which develops aspects of the development of multicultural-based religious, moral and cultural values ​​is carried out by inviting children to listen, observe and show concrete learning resources to children. In order for children to be able to teach, the teacher guides children with examples of good attitudes, behavior and words, conducts demonstrations and experiments. To encourage creativity to emerge so that the concept of adding is there the teacher provides motivation to children by giving praise, appreciating children. Religious and moral values ​​are in accordance with their beliefs through Imtaq activities according to their respective religions. To support culture, teachers introduce cultural products such as folk songs and culture-based extracurricular activities. (3) The supporting factors are having teachers of different religions and ethnicities, good communication, good interaction with adequate facilities and infrastructure, human resources who have a passion for learning and positive parental responses. The inhibiting factor is that the institution does not yet have Buddhist and Hindu teachers while they have students of that religion due to limited funds, inadequate IT, lack of socialization about multiculturalism, and lack of media on diversity posters placed in the classroom and teacher's office.